Empirical time-dependent tortuosity relations for hydrating mortar mixtures based on modified Archie's law. (20th May 2018) - Rangelov, Milena; Nassiri, Somayeh
Highlights: Mortar mixes were tested for time-dependent formation factor ( FF ) & tortuosity ( m ). FF and m both increase with curing time, decrease in w/cm, and increase in SCM. m was correlated to parameters of pore size distribution. m follows pore system refinement and an increase in non-uniformity of pore sizes. Abstract: Using sensor-based electrical data, empirical time-dependent tortuosity ( τ ) formulas as functions of pore size distribution (PSD) parameters were developed for 12 hydrating mortar mixtures. The inverse of the formation factor ( FF ) was used to obtain Archie's exponent ( m ), which is an indicator of tortuosity. PSD parameters were inferred from theoretical water vapor sorption isotherms. The results clarify the effects of curing time and mixture design on FF and tortuosity. Additionally, it is shown that m correlates with pore system refinement and increase in disparity of pore sizes, suggesting the usefulness of this parameter in describing pore system's intricacy.